STRATEGI EDUKATIF DALAM MENINGKATKAN KESADARAN PENGUATAN IDENTITAS BUDAYA MELALUI PELESTARIAN BAHASA SUNDA DI ERA DIGITAL - Duanty, Kinta; Nur Shadrina, Dhaifin; Choirut Nisa, Riri; Zahra Ningtyas, Dinda; Fatimah Zahra, Shalika; Tji Beng, Jap (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The Sundanese language, as part of Indonesia's cultural identity, has experienced a decline in the number of speakers, especially among the younger generation due to the influence of globalization, the dominance of Indonesian and foreign languages, and changes in communication patterns in the digital age. This study aims to examine the preservation strategies for the Sundanese language through digital technology and to identify the obstacles encountered in the process. This study uses a scoping review method based on the PRISMA framework. The researcher collected six scholarly articles through Google Scholar using the PCC (population, concept, context) criteria, then conducted selection, data extraction, and analysis based on the relevance of the topic of Sundanese language preservation in the digital era. The results show the use of digital technology through social media (Instagram, TikTok, YouTube), learning sites such as learningsundanese.com, voice-based dictionary applications, and augmented reality media. Social media is used to disseminate creative content such as Rebo Nyunda and Sundanese language parodies, while websites and applications provide interactive learning. However, obstacles such as limited ideas, technical issues, low public interest, and the perception that digitization may diminish cultural value are encountered. Several ways to preserve the Sundanese language in the digital age include: (a) developing digital content that is engaging and culturally appropriate for Sundanese, (b) developing user-friendly media for independent use, and (c) using media that makes language learning more enjoyable. Collaboration between the government, educators, and digital creators, along with the promotion of digital literacy and cultural pride among the younger generation, has proven effective in supporting the preservation of regional languages. ABSTRAK Bahasa Sunda sebagai bagian dari identitas budaya Indonesia mengalami penurunan jumlah penutur, terutama di kalangan generasi muda akibat pengaruh globalisasi, dominasi bahasa Indonesia dan bahasa asing, serta perubahan pola komunikasi di era digital. Penelitian ini bertujuan mengkaji strategi pelestarian Bahasa Sunda melalui teknologi digital dan mengidentifikasi hambatan yang dihadapi dalam proses tersebut. Penelitian ini menggunakan metode scoping review berdasarkan kerangka PRISMA. Peneliti mengumpulkan enam literatur ilmiah melalui Google Scholar menggunakan kriteria PCC (population, concept, context), kemudian melakukan seleksi, ekstraksi data, dan analisis berdasarkan kesesuaian topik pelestarian Bahasa Sunda di era digital. Hasil penelitian menunjukkan pemanfaatan teknologi digital melalui media sosial (Instagram, TikTok, YouTube), situs pembelajaran seperti learningsundanese.com, aplikasi kamus berbasis suara, serta media augmented reality. Media sosial digunakan untuk menyebarkan konten kreatif seperti Rebo Nyunda dan parodi Bahasa Sunda, sementara situs dan aplikasi menyediakan pembelajaran interaktif. Namun, terdapat hambatan seperti keterbatasan ide, masalah teknis, rendahnya minat masyarakat, dan anggapan bahwa digitalisasi dapat mengurangi nilai budaya. Beberapa cara pelestarian bahasa Sunda di era digital antara lain: (a) pengembangan konten digital yang menarik dan sesuai budaya Sunda, (b) pengembangan media yang mudah digunakan secara mandiri, dan (c) penggunaan media yang menyenangkan dalam pembelajaran bahasa. Kolaborasi antara pemerintah, pendidik, dan kreator digital, serta peningkatan literasi digital dan kebanggaan budaya di kalangan generasi muda terbukti efektif mendukung pelestarian bahasa daerah.